FORGING A DIPLOMATIC IDENTITY: HISTORICAL PERSPECTIVES ON NIGERIA’S FOREIGN POLICYAT INDEPENDENCE - Williams, Amah Maclean (AKSU Annals of Sustainable Development, 2025)
The attainment of independence in 1960 marked a defining moment in Nigeria’s diplomatic history, laying the foundation for its foreign policy orientation. As the most populous African state and a newly sovereign actor, Nigeria emerged into a world that was deeply divided along ideological lines, hence, the nation was confronted with the dual challenge of crafting a diplomatic identity while navigating Cold War rivalries, regional expectations, and domestic imperatives. This study therefore examines how Nigeria forged its foreign policy identity at independence by providing a historical perspective on the formation of Nigeria’s foreign policy at independence, interrogating the underlying principles, strategic choices, and external influences that shaped its early direction. Drawing on archival records, speeches, and contemporary analyses, the paper examines the Balewa doctrine which highlighted the centrality of Afrocentrism, non-alignment, and economic diplomacy as key guiding doctrines. It argues that Nigeria’s foreign policy in 1960 was not merely reactive to global pressures but reflected deliberate efforts to project leadership in Africa, safeguard sovereignty, and balance external partnerships with national interests. Furthermore, the study situates these choices within the broader historical context of decolonization, highlighting the influence of Pan-African ideals and the aspiration to resist neocolonial domination. By analyzing the historical making of Nigeria’s foreign policy at independence, the paper underscores the enduring relevance of these foundational choices in shaping subsequent diplomatic trajectories. Ultimately, this historical inquiry contributes to the understanding of how newly independent states in the postcolonial era constructed foreign policy identities amidst complex global and regional dynamics.